Iron Regulatory Mechanisms in Saccharomyces cerevisiae - Ramos-Alonso, Lucía; Romero, Antonia María; Martínez-Pastor, María Teresa; Puig, Sergi (Frontiers in Microbiology, 2020)
Iron is an essential micronutrient for all eukaryotic organisms because it participates as a redox cofactor in many cellular processes. However, excess iron can damage cells since it promotes the generation of reactive oxygen species. The budding yeast Saccharomyces cerevisiae has been used as a model organism to study the adaptation of eukaryotic cells to changes in iron availability. Upon iron deficiency, yeast utilizes two transcription factors, Aft1 and Aft2, to activate the expression of a set of genes known as the iron regulon, which are implicated in iron uptake, recycling and mobilization. Moreover, Aft1 and Aft2 activate the expression of Cth2, an mRNA-binding protein that limits the expression of genes encoding for iron-containing proteins or that participate in iron-using processes. Cth2 contributes to prioritize iron utilization in particular pathways over other highly iron-consuming and non-essential processes including mitochondrial respiration. Recent studies have revealed that iron deficiency also alters many other metabolic routes including amino acid and lipid synthesis, the mitochondrial retrograde response, transcription, translation and deoxyribonucleotide synthesis; and activates the DNA damage and general stress responses. At high iron levels, the yeast Yap5, Msn2, and Msn4 transcription factors activate the expression of a vacuolar iron importer called Ccc1, which is the most important high-iron protecting factor devoted to detoxify excess cytosolic iron that is stored into the vacuole for its mobilization upon scarcity. The complete sequencing and annotation of many yeast genomes is starting to unveil the diversity and evolution of the iron homeostasis network in this species.